From Apathy to Vigilance: Young Adolescents' Reactions to the Unite the Right Rally in Charlottesville. (22nd November 2020) - Williams, Joanna L.; Johnson, Haley E.; Mims, Lauren C.; Dickerson, Kimalee C.; Negrete, Andrea; Seward, Miray
Abstract : The present study examined middle school students' responses to the 2017 Unite the Right rally in Charlottesville, Virginia. Using a consensual qualitative research approach, we analyzed interviews from 73 local, seventh‐grade students (58% female; 55% students of color) to explore the range of students' emotional responses and cognitive engagement with the events. The resulting six profiles document heterogeneity in meaning‐making and personal impacts across youth. Individual and social factors including race and ethnic identity varied across profiles. Many students of color expressed fear and vigilance toward racial violence while many White students expressed sadness and sympathy. We discuss the role of developmental factors in students' reactions as well as implications for supporting early adolescents in the wake of bias‐motivated violence.